Delayed diagnosis of phenylketonuria – a case report of two siblings. (May 2014) - Narayanan, Deepa; Barski, Robert; Henderson, Mick J; Luvai, Ahai; Chandrajay, Deepak; Stainforth, Collette; Bradley, Jacqueline; Rogozinski, Hazel; Sharma, Reena
Phenylketonuria (PKU), is an autosomal recessive condition affecting the amino acid metabolism. The UK National newborn screening programme was commenced in 1969 and PKU is one among the five conditions included in the screening programme. We present the case history of two siblings of a family with a delayed diagnosis of PKU. This case history highlights such an occurrence. PKU should be considered as an important differential in the diagnosis of adult patients with learning difficulties, seizures and behavioural problems. It would be prudent to instigate plasma and urine amino/organic acid analyses in adult patients with unexplained neuropsychological manifestations.